A sex-related, multivariable statistical analysis of screen-time use in relation to dietary habits, among Greek young adults: an epidemiological study - Panagiotakou, Eleni-Evgenia; Kassimatis, Emmanouil; Gkoletsos, Evangelos -Marios; Kokkinelou, Eugenia; Tsourti, Passifai; Psykou, Sofia; Panagiotakos, Demosthenes (Health & Research Journal, 2025)
Background: Studies assessing screen time use in relation to lifestyle factors have predominantly concentrated on children and adolescents. Very few studies have been carried out on adult populations. The aim of this study was to investigate the association between time spent on screen (for work, education, entertainment), with dietary habits, among Greek young adults. Methods and Material: This is a cross-sectional study, based on convenience sampling of 687 adults (522 females), 18-30 years old, that was conducted on May 2023, in Greece. A structured questionnaire was used in which participants were asked about on screen-time habits (i.e., cellphone/tablet, television, computer/laptop), regarding work, education and entertainment, as well as various lifestyle characteristics, including dietary habits. Univariate and multivariate statistical methods were applied to explore the research hypothesis. Results: Mean daily screen time was 5±4 hours for work and 6±3.5 hours for entertainment. Unfavorable behaviors regarding excess screen time use and unhealthy dietary habits, were revealed. No significant association was observed between screen time use and adherence to the Mediterranean diet, when the analysis was stratified by sex. Conclusion: An association between screen time use and unhealthy dietary habits was revealed among young adults, which in the long-term may significantly influence their health status.